Trends and cycles in U.S. job mobility - Damir Stijepic (The Manchester School, 2021)
Recent studies document a decline in U.S. labor-market fluidity from as early as the 1970s on. Making use of the Annual Social and Economic supplement to the Current Population Survey, I uncover a pronounced increase in job-to-job mobility from the 1970s to the 1990s, i.e. the annual share of continuously employed job-to-job movers rises from 5.9% of the labor force in 1975–1979 to 8.8% in 1995–1999. Job-to-job mobility exhibits a downward trend only since the turn of the millennium. In order to provide a formal economic interpretation, I additionally estimate the parameters of the random on-the-job search model. Furthermore, I document that job-to-job mobility has an unconditional correlation of -0.86 with the unemployment rate at business-cycle frequencies in 1975–2017, varying by around 3 percentage points over the business cycle.
Keywords: 330; business cycles; Current Population Survey; economic fluctuations; Fokker–Planck equation; job mobility; Kolmogorov forward equation; long-run trends; on-the-job search; productive efficiency; search and matching